Counting by 7s - Sloan, Holly Goldberg 1958- (New York : Dial Books for Young Readers, 2013)
Twelve-year-old genius and outsider Willow Chance must figure out how to connect with other people and find a surrogate family for herself after her parents are killed in a car accident.
Keywords: Genius -- Juvenile fiction; Eccentrics and eccentricities -- Juvenile fiction; High schools -- Juvenile fiction; Schools -- Juvenile fiction; Orphans -- Juvenile fiction; Genius -- Fiction; Eccentrics and eccentricities -- Fiction; High schools -- Fiction; Schools -- Fiction; Orphans -- Fiction